Inside Back Cover: High‐Conductivity Two‐Dimensional Polyaniline Nanosheets Developed on Ice Surfaces (Angew. Chem. Int. Ed. 36/2015). Issue 36 (7th August 2015) - Choi, Il Young; Lee, Joungphil; Ahn, Hyungmin; Lee, Jinho; Choi, Hee Cheul; Park, Moon Jeong
<x xml:space="preserve">Abstract</x> Ice surfaces are used as removable hard templates to form two‐dimensional polyaniline nanosheets (green). As reported by M. J. Park and co‐workers in their Communication on page 10497 ff., high electrical conductivity was obtained for the nanosheets (>35 S cm−1). The polyaniline nanosheet can be easily transferred onto various types of substrates by float‐off from the ice surfaces, and the nanosheets can be patterned into any shape using predetermined masks.